Transcriptome profiling of cynomolgus macaque (Macaca fascicularis Raffles) from Peninsular Malaysia - Uli, Joey Ee (2017)
The cynomolgus macaque (Macaca fascicularis) is an extensively utilised nonhuman primate model for biomedical research due to its biological, behavioural, and genetic similarities to humans. Genomic information of cynomolgus macaque is vital for research in various fields, however, there is presently a shortage of genomic information on the Malaysian cynomolgus macaque. This study aimed to sequence, assemble, annotate, and profile the Peninsular Malaysian cynomolgus macaque transcriptome derived from five tissues, kidney, liver, lymph node, spleen, and thymus using RNA sequencing (RNA-Seq) technology. Tissues were harvested from three male wild cynomolgus macaques and were subjected to RNA extraction, RNA-Seq library preparation, and sequencing utilising the Illumina Hi-Seq 2500 sequencer. A total of 268,287,769 paired-end 75 base pair sequencing reads were obtained from the sequencing run. Filtered sequence reads were mapped to the M. fascicularis reference genome using CLC Genomics Workbench, with the overall mapping percentage of the sequence reads ranging from 44-69%. Differential gene expression analysis between four tissue comparisons revealed 5473 differentially expressed genes (DEGs) between kidney and liver, 574 DEGs between lymph and spleen, 5402 DEGs between lymph and thymus, and 7008 DEGs between spleen and thymus. The number of tissue-specific genes identified in kidney, liver, lymph, spleen, and thymus tissues were 310, 154, 2156, 169, and 143 genes respectively. Expressed genes were categorised to Gene Ontology (GO) and KEGG pathway categories using Panther Database and DAVID Bioinformatics Resources respectively. GO terms with the highest number of associated expressed genes were Cellular Process, Catalytic Activity, and Cell Part categories in the GO Biological Process, Molecular Function, and Cellular Component domains respectively. For pathway categorisation, the majority of expressed genes fall under Metabolism pathway (kidney and liver), Organismal systems (lymph), and Genetic information processing (spleen and thymus). Six metabolism-related pathway categories were enriched, which include Metabolic pathways, Biosynthesis of amino acids, Amino sugar and nucleotide sugar metabolism, Inositol phosphate metabolism, Pyruvate metabolism, and Oxidative phosphorylation, while five immune-related pathways were enriched, which include Complement and coagulation cascades, Platelet activation, Antigen processing and presentation, B cell receptor signalling pathway, and Intestinal immune network for IgA production. An additional eight immune-related pathways were identified, which include TNF signalling pathway, RNA degradation, Ras signalling pathway, Rap1 signalling pathway, Protein processing in endoplasmic reticulum, N-Glycan biosynthesis, Wnt signalling pathway, and NF-kappa B signalling pathway. RNA-Seq gene expression data were validated with NanoString nCounter Elements XT and real-time quantitative PCR assays. This study represents the first time the transcriptome of the Peninsular Malaysian cynomolgus macaque is sequenced via RNA-seq. Novel transcriptomic data will further enrich the present M. fascicularis genomic database and provide future research potentials involving the cynomolgus macaques, including novel transcript discovery, comparative genomic and / or transcriptomic studies with other closely related macaques, and the development of molecular markers for population genetic studies of the cynomolgus macaques in Malaysia and other regions.